Temporal-Spatial Measurement of Surface Morphological Evolution Time in Nanosecond Laser Irradiation on the Copper Film - Liu, Yuhan; Zhang, Jianguo; Shangguan, Shiyong; Qi, Dongfeng; Sun, Tengfei; Zheng, Hongyu (Frontiers in Physics, 2022)
In this research, the pump-probe imaging technology and the time-resolved transmittance measurements are used to investigate the transient time scale of the oxidation area, the dewetted melt pool, and the ablation-induced mass transport, and their dependence on the incident laser. Moreover, the evolution time of various morphologies have been studied through a certain delay time from 10 ns to 30 ns with different dynamic processes. Meanwhile, the underlying formation mechanism and the phase change pathway have been studied. In this regard, a nanosecond (ns) pulsed laser with 532 nm wavelength was used to fabricate nanostructures on the surface of the thin Copper (Cu) films. The observations confirmed that the oxidation process of Cu plays a significant role in the mechanism of laser fluence-dependent oxidation, melting, and ablation dynamics. The results revealed that the different characteristics of the Cu film are related to the incident laser pulse energy. Furthermore, the experimental evidence was in good agreement with the SEM images and the Raman spectra. It is found that the Cu2O surface-rim with a central hole could be fabricated with the laser fluences above the ablation threshold. Although, for the laser fluences below the ablation threshold, the Cu2O phase can be formed in the central region.